1.
1)
38² - 64 = 38² - 8² = (38 - 8)(38 +8) = 30 * 46 = 1380,
2.
1)
2в² - 18 = 2 * (в² - 9) = 2 * (в - 3)(в + 3),
3)
81х² - 18ху + у² + 63х - 7у = (81х² - 18ху + у²) + (63х - 7у) =
= (9х - у)² + 7*(9х - у) = (9х - у)(9х - у + 7),
4)
m² + n² + 2mn = (m + n)².
3.
а)
(8 - 2n)(8 + 2n) + (9 + 2n)² - 64 = 64 - 4n² + 81 + 36n + 4n² - 64 =
= 36n + 81 = 9(4n + 9),
б)
(3х - 8)² + (4х - 8)(4х + 8) = 9х² - 48х + 64 + 16х² - 64 = 25х² - 48х,
при х=-2:
25 * (-2)² - 48 * (-2) = 100 + 96 = 196,
4.
1 число - х,
2 число - (х+2),
(х+2)² - х² = 188,
х² + 4х + 4 - х² = 188,
4х = 184,
х = 46 - 1 число,
х+2 = 46+2 = 48 - 2 число
D(y)∈(-∞;∞)
y(-x)=-2/3x³-x²+4x+5 ни четная и ни нечетная
y`=2x²-2x-4=0
x²-x-2=0
x1+x2=1 U x1*x2=-2
x1=-1 U x2=2
+ _ +
(-1)(2)
возр max убыв min возр
ymax=y(-1)=-2/3-1+4+5=7 1/3
ymin=y(2)=16/3-4-8+5=10 1/3-12=-1 2/3
y``=4x-2=0
x=0,5
y(0,5)=1/12-1/4-2+5=2 2/6
(0,5;2 2/6)-точка перегиба
_ +
(0,5)
выпук вверх вогн вниз
Объяснение:
Раскрываем скобки :
n(n+5)-(n-3)(n+2)=n^2+5n-n^2+n-6=6n-6=6*(n-1)
Выражение кратно 6.
по действиям
1) n*(n+5)=n^2+5n
2) (n-3)*(n+2)=n^2-n-6
3) разность 6*(n-1)
кратна 6.